Enhancing Atomic Force Microscopy Sample Preparation Using a Modified Microwave-Assisted Drying System - Ilham Alkian; Lulut Tutik M. R.; Heri Sutanto (Akademi Inovasi Indonesia, 2024)
Atomic Force Microscopy (AFM) is widely used for high-resolution topographic imaging, but sample preparation remains a critical factor influencing image quality. Wet preparation techniques improve nanoparticle dispersion but often introduce residual solvent layers that degrade imaging performance. This study investigates a modified microwave-assisted drying system designed to enhance AFM sample preparation. A commercial microwave was adapted with precise power, temperature, and time controls to optimize drying conditions and minimize aggregation. Various sample preparation methods, including dry preparation, conventional wet preparation, and microwave-assisted drying, were evaluated. AFM characterization showed that the modified microwave system produced samples with more uniform morphology, reduced particle aggregation, and improved topographic resolution. Contact angle measurements indicated enhanced solvent removal, leading to increased hydrophobicity and better substrate interaction. These results demonstrate that controlled microwave-assisted drying is an effective strategy for improving AFM imaging quality, offering a practical alternative to conventional drying methods.